Bioethics in search of principles: the person - Possenti, Vittorio (Medicina e Morale, 1992)
This study first states that the very meaning of the ethical undertaking in human life is disputed. It considers indispensable that man asks himself about the meaning of "being moral" that the author identifies in the search for the light of good in the more generai field of the opening to being. From this one can see that the bioethical problems based on formal-abstract models of rationality, of logical-formal or on "moral contractualism" lead to bioethics that have little content and not much sense. From this introduction, the investigation on the person in the "suspension of haste" takes on an emblematic value and constitutes a necessary crossroad for the solution of many of the problems of bioethics. Biological sciences can not know anything about the person: this belongs to the philosophical method, that is "ontosophical". The author suggests an approach in bioethics according to which reality, life and human beings are considered from an ontological point of view. The originality and specificity of being a person emerges from this point of view and this is "ontological personalism". The study continues with the criticai analysis of the contemporaty philosophical answers to the two following questions: ''what is a person?" and "who is a person?" and concludes with a section where arguments that support attribution of personal status to the human embryo, are developped.